2012
DOI: 10.1074/jbc.m111.294025
|View full text |Cite
|
Sign up to set email alerts
|

Tannic Acid Is a Natural β-Secretase Inhibitor That Prevents Cognitive Impairment and Mitigates Alzheimer-like Pathology in Transgenic Mice

Abstract: Background: Recent focus has been given to anti-amyloidogenic naturally occurring polyphenols known as flavonoids. Results:The polyphenol tannic acid prevented behavioral impairment and mitigated Alzheimer disease-like pathology. Conclusion: Tannic acid may be prophylactic for Alzheimer disease by inhibiting ␤-secretase activity and mitigating brain pathology. Significance: This nutraceutical approach offers a new class of drug for inhibiting ␤-secretase with few if any side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
107
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(117 citation statements)
references
References 75 publications
9
107
0
1
Order By: Relevance
“…This behavioral phenotype has been reported in cerebral amyloidosis mouse models (e.g. Tg2576 or PSAPP mice) (20,22,23,26,35), and it may reflect disinhibition because of cortical and/or hippocampal damage (25). Overall ANOVA disclosed the main effects of genotype (p Ͻ 0.001 for both locomotion and rearing scores) and treatment (p Ͻ 0.001 for both locomotion and rearing scores), and repeated-measures ANOVA followed by post hoc comparison revealed statistically significant differences between PSAPP-V mice and the other three groups of mice for both locomotion and rearing scores (Fig.…”
Section: Methylene Blue Treatment Reverses Behavioral Benefits Insupporting
confidence: 72%
See 2 more Smart Citations
“…This behavioral phenotype has been reported in cerebral amyloidosis mouse models (e.g. Tg2576 or PSAPP mice) (20,22,23,26,35), and it may reflect disinhibition because of cortical and/or hippocampal damage (25). Overall ANOVA disclosed the main effects of genotype (p Ͻ 0.001 for both locomotion and rearing scores) and treatment (p Ͻ 0.001 for both locomotion and rearing scores), and repeated-measures ANOVA followed by post hoc comparison revealed statistically significant differences between PSAPP-V mice and the other three groups of mice for both locomotion and rearing scores (Fig.…”
Section: Methylene Blue Treatment Reverses Behavioral Benefits Insupporting
confidence: 72%
“…Aged PSAPP mice had typical cerebral ␤-amyloid deposits (17,18,22,23). In fact, PSAPP-V mouse brains had 7.1-8.6% of cerebral ␤-amyloid burden at 18 months of age that distributed diffusely throughout RSC, EC, and H regions and was markedly and significantly reduced by 3.1-5.8% in all three PSAPP-MB brain regions, with greatest reduction in the EC (Figs.…”
Section: Methylene Blue Treatment Reverses Behavioral Benefits Inmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Also, brain parenchymal and cerebral vascular β-amyloid deposits were diminished in tannic acid treated PSAPP mice, suggesting that it acts as a natural β-secretase inhibitor. 66 Natural flavonoids were shown to potently inhibit BACE-1 activity and reduce the level of secreted Aβ in primary cortical neurons, 67 whereas epigallocatechin-3-gallate and curcumin suppress amyloid beta-induced BACE-1 upregulation in neuronal cultures. 68 Several studies have focused on studying the beneficial properties of regular intake of green tea.…”
Section: ■ Flavonoidsmentioning
confidence: 99%
“…Although the exact mechanisms underlying these improvements are not clear, it has been suggested that polyphenols may delay the initiation of and/or slow the progression of Alzheimer's Disease (AD)-like pathology, including a potential to inhibit neuronal apoptosis triggered by neurotoxic species (e.g. oxidative stress and neuroinflammation) (Vauzour et al, 2007a;Mori et al, 2012;Cox et al, 2015). Polyphenols can reduce amyloid-beta (Ab) plaque pathology (Hirohata et al, 2007;Amit et al, 2008;Ehrnhoefer et al, 2008;Ono et al, 2008;Wang et al, 2014), and therefore they could have utility in AD beyond anti-Ab processing .…”
Section: Effects Of Polyphenols On Age-related Cognitive Decline and mentioning
confidence: 99%